Gagasan Maqashid Syari’ah Imam Asy-Syatibi dan Implementasinya dalam Bidang Ekonomi dan Keuangan Syariah - Ma’lufah, Ulfatul; Muhajirin, Muhajirin (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to study the concept of maqashid sharia according to Imam Asy-Syatibi and its application in sharia economics. Imam Asy-Syatibi is a figure who developed the concept of maqashid sharia, which emphasizes achieving the benefit of the people by using the principle of maslahah murlahah in determining Islamic law. The research method used is library research by looking for references and previous studies sourced from books, journals and articles. The results of the research show that Imam Asy-Syatibi's maqashid sharia covers important aspects such as ownership, production, consumption, distribution, and fiscal policy, so that his thinking is worthy of being the basis for implementing maqashid sharia in sharia economics and finance to achieve the welfare of the people because it is able to play a role important in guiding Islamic economic policies and practices.